The Fluid Identity of Enola Holmes in Nancy Springer's an Enola Holmes Mystery: The Case of the Missing Marquess - Muafa, Kamilia Yasmin; Anam, Zuhrul (LPPM Universitas Bumigora Mataram, 2024)
In the literature field, the investigation of self-identity within cultural and historical contexts offers insights into the life experience and self-belief of the character. This article aims to examine the portrayal of self-identity in An Enola Holmes Mystery: The Case of the Missing Marquess, a book from Nancy Springer’s Enola Holmes series, utilizing post-structuralist literary theory as its theoretical foundation. The article explores how the main character, Enola Holmes, negotiates and navigates her self-identity in a patriarchal Victorian society. It also investigates Enola’s identity construction within traditional gender norms and expectations. This study employed a descriptive methodology to examine the dynamicity of its main characters and plots. Referring to Jacques Derrida’s post-structuralism theory and the concepts of differance, the findings revealed that the fluidity of Enola Holmes’ self-identity challenges the traditional gender roles and binary expectations in the period, which emphasizes the instability of the meaning and self-identity. The primary findings show the character’s fluid identity, such as rejecting traditional gender roles, embracing individuality, affirming independence, and challenging authority figures. The second one is the character’s responses, such as seeking validation, desire for freedom, frustration with double standards, longing for acceptance, and oppression in femininity. The last one is the character’s self-discovery, such as embracing fluid identity and recognizing one’s value of femininity.The implications of this study are to enrich the literary study and to encourage readers and academics to critically engage with the literary text by exploring complex concepts like self-identity and post-structuralism.